If You Think You No Longer Need to Know Anything About the Rule Against Perpetuities, Then Read This! - David M. Becker (Washington University Law Quarterly, 1996)
Lawyers have dreaded the common-law rule against perpetuities for many generations, and for good reason. It is difficult to teach and to comprehend; consequently, most lawyers have never mastered it. Additionally, the rule is quirky, difficult to justify, and unfair. In recent years perpetuities law has undergone substantial legislative reform. The majority of these efforts has taken the form of "wait-and-see" conversions of the common-law rule. And the most significant and prevalent of these reforms has been the Uniform Statutory Rule Against Perpetuities ("USRAP"), which offers "wait-and-see" for a period of ninety years coupled with reformation of interests that fail to satisfy its test. Undoubtedly, lawyers and law students will celebrate the arrival of these reforms and the end of the common-law rule's reign of terror. They will celebrate the ostensible obsolescence of an entire body of law, one they seldom understood and often ignored. But should they? This article asks the question: What must estate planners in every jurisdiction know about the common-law rule against perpetuities? The answer: A lot!
Keywords: Perpetuities; Estate planning